(untitled) (Global Journal of Management and Business Research, 2015)
Over the last few decades, the global business environment has been changing rapidly, especially after the computer revolution. The world is now a global village. Apart from technological advances, the successful completion of a project often depends upon HR activities. This study is conducted to compare the Muslim culture and Western culture in the light of the experience of expatriates. Many expatriates fail in their international assignments in Muslim countries. Research will find out why, in spite of training, expatriates are failing in international assignments. 350 Questionnaires were distributed among workers; 235 questionnaires are validated. These workers are from different countries, especially western countries and working or have worked in different Muslim countries e.g. Pakistan, Turkey, Saudi Arabia, and Afghanistan. The research results are limited to a few Muslim countries and may not give an overall picture of the Muslim world. It has been observed in the results that expatriates failure occurred because of cultural reasons. The expatriates and their families are facing cultural problems. In spite of training, a lack of essential knowledge about Muslims is missing in few expatriates.